Understanding global mobility of dietetic talents: a survey study of overseas-educated dietetic returnees in China - Yajie Zhang; Luyue Zheng; Xiaoli Wang; Xiuhua Shen; Yi Feng; Yang Niu; Wei Cai (Globalization and Health)
Abstract Background Although international mobility of medical personnel has gained scholarly attention, there has been limited empirical research on overseas-educated dietetic professionals. China has experienced a notable return of highly skilled professionals. This study aims to explore the experiences of Chinese overseas-educated dietetic returnees, focusing on their practice areas, job satisfaction, motivations for returning, post-return challenges, and career development strategies. Methods A web-based survey, conducted from July to December 2022, targeted dietetic returnees with degree(s) from institutions outside mainland China. Participants were recruited from professional group chats on a social media platform. Job satisfaction was assessed using a 7-item scale, with responses ranging from 0 to 5 for each item. Its internal consistency was evaluated via Cronbach’s alpha. Responses were analyzed using descriptive statistics, t tests, and ANOVA. A multivariate regression helps further predict job satisfaction. Thematic analysis guides the analysis of an open-ended question. Results Participants (N = 138) were mainly female (86.2%), had a master’s degree (79.0%), and had studied in the United States (37.7%). Clinical roles dominated post-return employment, but returnees also pursued biomedicine, biotechnology, and media. The mean job satisfaction score of 3.39 indicated moderate satisfaction. Job satisfaction varied across subgroups (e.g., older participants); however, in the multivariable regression model, only salary level remained a significant predictor. Key motivations for returning included familial ties, societal connections, and a desire to contribute to home country development. Returnees identified limited domestic networking connections as a top challenge. Meanwhile, they demonstrated agency in navigating post-return career development, such as by leveraging transnational social networks. Returnees also envisioned systematic workforce changes, such as improving licensure and regulation for foreign-trained professionals. Conclusion Returnees have diverse career pathways. Post-return job satisfaction, however, was significantly predicted only by salary level, emphasizing the critical role of compensation and economic viability in sustaining careers in the dietetic field. Our findings suggest that while returnees were primarily motivated by personal and cultural factors, they faced significant re-entry challenges that warrant attention from educators and policymakers. Future research should explore the global mobility of the dietetic profession and its potential to contribute to ‘brain gain’ in China’s healthcare sector.